A COMPARATIVE-CORRELATIONAL STUDY OF UPPER ELEMENTARY AND MIDDLE SCHOOL STUDENTS’ PERCEPTIONS OF PARENTAL INFLUENCE AND SELF-EFFICACY FOR LEARNING MATHEMATICS WITH MATHEMATICS ACADEMIC ACHIEVEMENT AT PAN-ASIA INTERNATIONAL SCHOOL, BANGKOK, THAILAND - AKKUS, SERPIL; LYNCH, RICHARD (Scholar: Human Sciences, 2022)
The purpose of this study was to investigate whether there was a significant relationship between perceived parental influence and self-efficacy for learning mathematics with mathematics academic achievement and also whether there was a significant difference in perceived parental influence on learning mathematics and in students’ self-efficacy for learning mathematics for upper elementary and middle school students at Pan-Asia International School Bangkok, Thailand. The research was conducted among 41 upper elementary students and 49 middle school students enrolled in the academic year 2020 - 2021. The Students’ Perceptions of Parental Influence and Self-Efficacy for Learning Mathematics Questionnaire was used to collect data to measure students’ levels of perceived parental influence and self-efficacy for learning mathematics. The November 2020 Measures of Academic Progress (MAP) mathematics scores were used to determine the students’ mathematics academic achievement. Descriptive statistics such as means, standard deviations, independent samples t-test, and multiple correlation coefficient analysis were used to analyze the data. A multiple correlation coefficient analysis revealed there was a significant, positive, and moderately strong multiple correlations between self-efficacy for learning mathematics and mathematics academic achievement for both upper elementary and middle school students. However, there was a very weak and positive correlation between upper elementary students’ perceptions of parental influence on learning mathematics and mathematics academic achievement. It also indicated that there was a very weak and negative correlation between middle school students’ perceptions of parental influence on learning mathematics and mathematics academic achievement. Independent samples t-test revealed that there was a significant difference between the upper elementary and middle school students’ perceptions of parental influence on learning mathematics, while no significant difference between the upper elementary and middle school students’ self-efficacy for learning mathematics.